HUBUNGAN MUTU PELAYANAN KESEHATAN RUMAH SAKIT DENGAN TINGKAT KEPUASAN PASIEN RAWAT INAP DI RS ADI HUSADA KAPASARI - Hermanto Wijaya; Irawati Marga; Ariawan Wangsa; Afif Kurniawan (LPPM Universitas Awal Bros, 2021)
Public demand for adequate health services is increasing. This is due to changes in disease patterns, demographic structures, developments in science and technology, and the community's economy. Patients will feel satisfied if their expectations for health services are met. To increase patient satisfaction with health services, the quality of service must also be improved. The quality of health services is the compatibility between the health services provided and the patient's needs or compliance with the provisions of service standards. This study used a cross sectional design on a sample of 20 patients who were treated in the D2 inpatient room at Adi Husada Kapasari Hospital on 13 October – 13 December 2019. As many as 55% of respondents stated that the quality of health services provided by nurses was quite good, 40% of patients stated very satisfied with the quality of service. The chi-square result shows a sig value of 0.027 (P<0.05). This means that there is a relationship between health services and the level of patient satisfaction. The quality of service and the level of patient satisfaction in hospitals are two things that are very closely related. Increasing public demands force hospitals to continue to innovate and improve the quality of their services to patients.​